Tax evasion and welfare fraud: do punishments fit the crime or the perception of the crime?. Issue 4 (6th November 2017) - Marriott, Lisa; Sim, Dalice
Abstract : Purpose: Individuals with fewer resources often receive more punitive treatment in the justice system than those who are more privileged. This situation is frequently justified with reference to societal preferences. To test the accuracy of this justification, the purpose of this study is to report on the extent to which the different treatments of tax evaders and welfare fraudsters in the Australian and New Zealand justice systems reflect the views of these societies. Design/methodology/approach: Attitudes are captured in a survey with 3, 000 respondents in Australia and New Zealand. Findings: When asked directly, the majority of respondents (58 per cent) perceive no difference in people committing welfare fraud or tax evasion. However, responses to presented scenarios on tax evasion and welfare fraud show different tolerances for each crime. When provided with scenarios including crimes and criminals, results show that survey respondents see tax evasion as a less serious crime. However, when asked about their own propensity to commit the same offence, respondents indicate that they are more likely to engage in welfare fraud than tax evasion. The authors also report on factors that have an impact on individual's attitudes towards tax evasion and welfare fraud. Social implications: The survey results do not clearly show more punitive attitudes towards tax evasion or welfare fraud. Thus, the authors do not find support for the suggestion that the harsher treatment of welfare fraud can be justified with reference to society's views. Originality/value: The study reports on original survey research.